Breast cancer and hormonal contraceptives: further results. Collaborative Group on Hormonal Factors in Breast Cancer. - Beral, V (1996)
The Collaborative Group on Hormonal Factors in Breast Cancer has brought together and reanalysed the worldwide epidemiological evidence on breast cancer risk and use of hormonal contraceptives. Original data from 54 studies, representing about 90% of the information available on the topic, were collected, checked and analysed centrally. The 54 studies were performed in 26 countries and include a total of 53,297 women with breast cancer and 100,239 women without breast cancer. The studies were varied in their design, setting and timing. Most information came from case-control studies with controls chosen from the general population; most women resided in Europe or North America and most cancers were diagnosed during the 1980s. Overall 41% of the women with breast cancer and 40% of the women without breast cancer had used oral contraceptives at some time; the median age at first use was 26 years, the median duration of use was 3 years, the median year of first use was 1968, the median time since first use was 16 years, and the median time since last use was 9 years. The main findings, summarised elsewhere, are that there is a small increase in the risk of having breast cancer diagnosed in current users of combined oral contraceptives and in women who had stopped use in the past 10 years but that there is no evidence of an increase in the risk more than 10 years after stopping use. In addition, the cancers diagnosed in women who had used oral contraceptives tended to be less advanced clinically than the cancers diagnosed in women who had not used them. Despite the large number of possibilities investigated, few factors appeared to modify the main findings either in recent or in past users. For recent users who began use before age 20 the relative risks are higher than for recent users who began at older ages. For women whose use of oral contraceptives ceased more than 10 years before there was some suggestion of a reduction in breast cancer risk in certain subgroups, with a deficit of tumors that had spread beyond the breast, especially among women who had used preparations containing the highest doses of oestrogen and progestogen. These findings are unexpected and need to be confirmed. Although these data represent most of the epidemiological evidence on the topic to date, there is still insufficient information to comment reliably about the effects of specific types of oestrogen or of progestogen. What evidence there is suggests, however, no major differences in the effects for specific types of oestrogen or of progestogen and that the pattern of risk associated with use of hormonal contraceptives containing progestogens alone may be similar to that observed for preparations containing both oestrogens and progestogens. On the basis of these results, there is little difference between women who have and have not used combined oral contraceptives in terms of the estimated cumulative number of breast cancers diagnosed during the period from starting use up to 20 years after stopping. The cancers diagnosed in women who have used oral contraceptives are, however, less advanced clinically than the cancers diagnosed in never users. Further research is needed to establish whether the associations described here are due to earlier diagnosis of breast cancer in women who have used oral contraceptives, to the biological effects of the hormonal contraceptives or to a combination of both. Little information is as yet available about the effects on breast cancer risk of oral contraceptive use that ceased more than 20 years before and as such data accumulate it will be necessary to re-examine the worldwide evidence.